Cloning and expression in Escherichia coli of Serratia marcescens genes encoding prodigiosin biosynthesis. - Dauenhauer, S A (1984)
Prodigiosin, the bright red pigment produced by many strains of Serratia marcescens, is synthesized by a bifurcated pathway that terminates in the enzymatic condensation of the two final products, a monopyrrole and a bipyrrole . Sau3A fragments of S. marcescens ( Nima ) DNA were introduced into a strain of Escherichia coli K-12 by use of the cosmid vector pHC79 , and transformed clones were selected based on resistance to ampicillin. Among 879 transformants screened, 2 could be induced to synthesize prodigiosin when supplied with either one or both terminal products of the bifurcated pathway. Data are presented to support the idea that production of prodigiosin is not usually mediated by a plasmid.